STRENGTHENING THE COMPETITIVENESS OF MSMES THROUGH THE DIGITALIZATION OF PROMOTION AND INVENTORY SYSTEMS: IMPLEMENTATION AT DONAT MADU CIAHANJUANG, PATI REGENCY - Randika Shafly Fawwaz; Putri Aryo Jelang Fitri Khothimah; Anindya Putri Utami; Reni Nur Arifah; Yetty Yuliany K (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2025)
Community service (PKM) is part of the learning process that aims to integrate theory and practice in the business world. This activity was carried out at the Donat Madu Cihanjuang Pati MSME, a micro-enterprise in the culinary sector with great potential but facing various operational and managerial obstacles. The main focus of the activity was to analyze and provide solutions to the problems of suboptimal promotion and weak control of raw material inventory. The implementation method included field observation, interviews, SWOT analysis, and the Fishbone and USG (Urgency, Seriousness, Growth) approaches to identify and prioritize problems. The results of the activity showed that digital promotion efforts had not been optimally utilized even though the market share was still wide open. Furthermore, the lack of an inventory recording system caused inefficiencies in the production process, particularly in the procurement of raw materials such as eggs. As a solution, a student team assisted the MSME by creating promotional content templates for social media, brochure designs, and promotional pamphlets. In terms of operations, the team developed stock card templates, raw material formulas, and daily production planning. It is hoped that through this implementation, the Donat Madu MSME can improve production efficiency and expand its marketing reach, thereby strengthening its competitiveness in the local market. This program proves that student involvement in the business world has a real impact on the development of MSMEs.